Guidelines for Development of Area-Based Plantation of Rubber Commodity in Musi Rawas - Dian Eka Putra; Agus Darwa (Department of Development Economics, Universitas Sriwijaya, 2021)
There has not been a good integration among the central, provincial, and regional levels in the allocation of the budget, thus making the impact of plantation development activities less effective and efficient. This study aimed to analyze the potential of the region and create a pattern for the development of rubber commodity plantations in Musi Rawas District. This study was conducted by analyzing the data and literature review, conducting focus group discussions, mapping and digitizing the potential for rubber commodities using satellite imagery. With the position of the region that is included in the growing stage, the development of the area is directed first for on-farm development. The development of the region is carried out by increasing the production and productivity of rubber plants in Musi Rawas District by replanting and intensifying the rubber plants. The activity strategy focuses more on how to increase the productivity of rubber plants so as to produce high quality claret processing materials (BOKAR) and rubber wood. The development strategy is centered in Tuah Negeri sub-district as the center of the Area and other surrounding sub-districts as supporting Areas. Therefore, in order to achieve these production targets, the strategy taken in developing rubber-based plantation areas is the incorporation and strengthening of the rubber agribusiness system.